MoS2 nanoparticles and h-BN nanosheets from direct exfoliation of bulk powder: one-step synthesis method - Thripuranthaka, M.; Rout, Chandra Sekhar; Late, Dattatray J. (Materials Research Express, 2014)
We report facile synthesis of MoS2 nanoparticles and h-BN nanosheets using ultrasonication method in suitable solvents such as N-Methyl-2-pyrrolidone and ethylene glycol, respectively. The average size of MoS2 nanoparticles observed from TEM analysis were 4-5 nm and about a few hundreds of nm for h-BN nanosheets. Raman spectroscopy carried out on nanoparticle samples confirms the formation of MoS2 nanoparticles and h-BN nanosheets. UV-vis absorption and photoluminescence (PL) measurements carried out on the products show typical absorption and luminescence spectra of MoS2 and h-BN. Further, we attempted to decorate gold nanoparticles on nanosheets of MoS2 and h-BN which show subsequent change in Raman spectra due to charge transfer interaction.
Keywords: h-BN; MoS2; Nanoparticles; nanosheets; Optical properties